PERBANDINGAN METODE ORDINARY LEAST SQUARE (OLS) DAN REGRESI ROBUST - Ibnu Dharma Syahputra; Abdul Karim (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Human Development Index (HDI) is a comparative measurement of life expectancy, literacy, education. A country that is said to be advanced can be reflected if one of its reference is the Human Development Index (HDI), which of course explains how much human development in a country. Indonesia has human resources that can be explored and explored to show a significant index of human development. The Human Development Index (IPM) is a composite index that is influenced by health indicators represented by life expectancy (AHH), education indicators represented by the average school length (RLS) and economic indicators represented by public purchasing power (PPP) . Decentralization of Central Kalimantan Province is expected to make arrangements that can realize the life of the people of Central Kalimantan to be more prosperous and healthy. One of the elements in human development is to make the people to live longer and healthier lives. Data source used in this research is secondary data of HDI in Central Kalimantan obtained from Central Bureau of Statistics of Central Kalimantan Province 2014. Variable used in this research is endogenous variable (Y) and exogenous variable (X). Variable endogenus (Y) in the research that is HDI (percent) while the variable (X) in the study there are 3 that is Life Expectancy Numbers, Perkapita Revenue, Average Learning Length.Using OLS method and ROBUST method of both methods the best model that is on robotic methodKeywords: HDI, OLS, ROBUST